Comprehensive bactericidal activity of an ethanol-based hand gel in 15 seconds - Kampf Günter; Hollingsworth Angela (BMC, 2008)
Abstract Background Some studies indicate that the commonly recommended 30 s application time for the post contamination treatment of hands may not be necessary as the same effect may be achieved with some formulations in a shorter application time such as 15 s. Method We evaluated the bactericidal activity of an ethanol-based hand gel (Sterillium® Comfort Gel) within 15 s in a time-kill-test against 11 Gram-positive, 16 Gram-negative bacteria and 11 emerging bacterial pathogens. Each strain was evaluated in quadruplicate. Results The hand gel (85% ethanol, w/w) was found to reduce all 11 Gram-positive and all 16 Gram-negative bacteria by more than 5 log10 steps within 15 s, not only against the ATCC test strains but also against corresponding clinical isolates. In addition, a log10 reduction > 5 was observed against all tested emerging bacterial pathogens. Conclusion The ethanol-based hand gel was found to have a broad spectrum of bactericidal activity in only 15 s which includes the most common species causing nosocomial infections and the relevant emerging pathogens. Future research will hopefully help to find out if a shorter application time for the post contamination treatment of hands provides more benefits or more risks.